2016
DOI: 10.1152/ajpendo.00325.2015
|View full text |Cite
|
Sign up to set email alerts
|

Contracting C2C12 myotubes release CCL2 in an NF-κB-dependent manner to induce monocyte chemoattraction

Abstract: Miyatake S, Bilan PJ, Pillon NJ, Klip A. Contracting C2C12 myotubes release CCL2 in an NF-B-dependent manner to induce monocyte chemoattraction. Am J Physiol Endocrinol Metab 310: E160 -E170, 2016. First published November 10, 2015; doi:10.1152/ajpendo.00325.2015.-Muscle inflammation following exercise is characterized by expression of inflammatory cytokines and chemokines. Exercise also increases muscle macrophages derived from circulating monocytes. However, it is unknown whether muscle cells themselves attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…NFkB activation was necessary for the up-regulation of ccl2 expression upon EPS [15]. Here, we demonstrate that ATF3 is also necessary.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…NFkB activation was necessary for the up-regulation of ccl2 expression upon EPS [15]. Here, we demonstrate that ATF3 is also necessary.…”
Section: Discussionsupporting
confidence: 50%
“…We have previously shown in mice that endurance exercise increases ATF3 protein levels 3 h post-exercise [7]. Here, we electrically stimulated C 2 C 12 myotubes with a protocol that mimics endurance exercise in vitro [15], and analyzed the responses 3 h after. EPS increased atf3 mRNA and protein levels in C 2 C 12 myotubes, suggesting part of the ATF3 up-regulation in contracting skeletal muscle occurs in myofibers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides immune cells, the main source of chemokines in skeletal muscle, muscle fibers can also chemoattract myeloid cells secreting chemokines. We recently found that NF-κB is activated in C2C12 myotubes upon muscle contraction and upregulate C-C motif chemokine ligand (CCL) 2 secretion, inducing THP-1 monocyte chemoattraction 61. In addition, several CC chemokines including CCL2, which are the components of the largest family of chemokines, and chemoattractive for diverse inflammatory cells, showed increased expression in mdx muscle 62.…”
Section: Potential Drugs Targeting Inflammatory Mechanisms In Dmdmentioning
confidence: 99%